Thienylvinylenethienyl and Naphthalene Core Substituted with Triphenylamines—Highly Efficient Hole Transporting Materials and Their Comparative Study for Inverted Perovskite Solar Cells (Solar RRL 8∕2017). Issue 8 (August 2017) - Pham, Hong Duc; Hu, Hongwei; Feron, Krishna; Manzhos, Sergei; Wang, Hongxia; Lam, Yeng Ming; Sonar, Prashant
Abstract : Here, Pham et al. (article No.201700105 ) synthesize processable small molecular hole transporting materials (HTMs), TPA‐TVT‐TPA and TPA‐NAP‐TPA, using triphenylamine as common end capping groups with thienylvinylenethienyl and naphthalene cores, respectively. These HTMs have been successfully used in inverted devices of perovskite solar cells. The power conversion efficiency of these dopant‐free HTMs based devices is found to be of 16.32% for TPA‐TVT‐TPA and 14.63% for TPA‐NAP‐TPA. In particularly, TPA‐TVT‐TPA exhibits an impressive V oc of 1.07 V. The obtained performance is one of the highest performances in inverted perovskite layouts. The low‐price and a straightforward synthesis with an elegant scale up, makes these classes of materials important for the industry to produce high‐throughput printed perovskite solar cells for large area applications.